Relación entre el aburrimiento y la depresión en el lugar de trabajo - Pasco Rossell, Fiorella Esther (2021)
The relationship between job demands and mental health of workers is a topic of interest for researchers in the area of occupational psychology (Rosario-Hernández et al., 2020). Boredom at work is a common feeling; it is estimated that a quarter to 87% of the employees feel bored at least some times at work (van Hooff & van Hooft, 2014). However, when it lasts for a long time, it can lead to depression. The aim of this work is to identify the relationship between boredom and depression in the workplace, for which an applicated research of previous related studies to this topic was done. The PRISMA guidelines (Urrutia and Bonfill, 2013) were followed and the databases consulted were Scopus, EBSCO, Proquest and Researchgate, selecting eight articles to analyze boredom and depression at the workplace. Results show that there is a positive relationship between both variables, meaning greater boredom, greater depression. It was also found that there are variables that help to mitigate the appearance of depression and that boredom is also linked to anxiety and stress. Future research should homogenize the measurement of both variables in order to achieve greater cientific rigor.